Dark Energy Survey Year 3 results: Cosmology from cosmic shear and robustness to modeling uncertainty - Secco, L. F. (2022)
This work and its companion paper, Amon et al. [Phys. Rev. D 105, 023514 (2022)PRVDAQ2470-001010.1103/PhysRevD.105.023514], present cosmic shear measurements and cosmological constraints from over 100 million source galaxies in the Dark Energy Survey (DES) Year 3 data. We constrain the lensing amplitude parameter S8σ8ωm/0.3 at the 3% level in ΛCDM: S8=0.759-0.023+0.025 (68% CL). Our constraint is at the 2% level when using angular scale cuts that are optimized for the ΛCDM analysis: S8=0.772-0.017+0.018 (68% CL). With cosmic shear alone, we find no statistically significant constraint on the dark energy equation-of-state parameter at our present statistical power. We carry out our analysis blind, and compare our measurement with constraints from two other contemporary weak lensing experiments: the Kilo-Degree Survey (KiDS) and Hyper-Suprime Camera Subaru Strategic Program (HSC). We additionally quantify the agreement between our data and external constraints from the Cosmic Microwave Background (CMB). Our DES Y3 result under the assumption of ΛCDM is found to be in statistical agreement with Planck 2018, although favors a lower S8 than the CMB-inferred value by 2.3σ (a p-value of 0.02). This paper explores the robustness of these cosmic shear results to modeling of intrinsic alignments, the matter power spectrum and baryonic physics. We additionally explore the statistical preference of our data for intrinsic alignment models of different complexity. The fiducial cosmic shear model is tested using synthetic data, and we report no biases greater than 0.3σ in the plane of S8×ωm caused by uncertainties in the theoretical models.